Discovery of new tranylcypromine derivatives as highly potent LSD1 inhibitors. (1st June 2021) - Huang, Ming-Jie; Guo, Jia-Wen; Fu, Yun-Dong; You, Ya-Zhen; Xu, Wen-Yu; Song, Ting-Yu; Li, Ran; Chen, Zi-Tong; Huang, Li-Hua; Liu, Hong-Min
Graphical abstract: Abstract: Tranylcypromine (TCP)-based structural modifications lead to the discovery of new LSD1 inhibitors, of which compounds 26b and 29b effectively inhibit LSD1 with the IC50 values of 17 and 11 nM, respectively and also show good selectivity over MAO-B. Mechanistic studies showed that compound 29b concentration-dependently induced H3K4me1/2 accumulation in LSD1 overexpressed MGC-803 cells and also inhibited metastasis of MGC-803 cells. Collectively, both compounds could be promising lead compounds for further investigation.